The development and application of eDNA metabarcoding for aquatic biomonitoring in Australia’s Indian Ocean region - West, Katrina Marie (Curtin University, 2020)
The advent of environmental DNA (eDNA) metabarcoding, a technique which characterises DNA shed by both aquatic and terrestrial organisms into their immediate surroundings, has considerable potential to rapidly identify complex species assemblages for biomonitoring purposes. There are few studies however, that have applied these technologies for aquatic surveying in Australia. This PhD thesis furthers the development and application of eDNA metabarcoding across a variety of aquatic ecosystems and spatial scales within Australia’s Indian Ocean region.